Povezanost koordinacije z nekaterimi drugimi motoričnimi sposobnostmi - Muhič, Miran (Revija za elementarno izobraževanje, 2016)
Correlation of Coordination with some Other Motor Abilities. The research sought the causal non-experimental method to explain the correlation of coordination with some other motor abilities. In the non-random sample from the actual population 22 children aged 2 to 3 years and 34 children aged 5 to 6 years were included. We used nine motor tests as the measuring instrument. Spearman’s rank correlation coefficient was calculated to determine the relations of the results of each motor test. We have found that in children aged 2 to 3 years a moderate correlation between results of test coordination and test coordination/explosive strength (p < 0.05) is detected. In children aged 5 to 6 years a strong correlation shows of the results of the test of coordination with other motor tests (p < 0.01; p < 0.05). We assume that the reason for the moderate correlation of results of the test of coordination with the test of coordination/explosive strength in young children is the time deficit in the cerebellum due to insufficient motor experience. With conditionally more motor experience, which children acquire in later years, motor control improves and consequently allows quality execution of motor tasks.